EVALUATION OF THE THERMAL PERFORMANCE OF CALVES' SHELTER WITH ECO-LINING OF WOOD PARTICLES AND SISAL FIBER - Cabral, M. R.; Nakanishi, E. Y.; Fiorelli, J.; Savastano Jr, H. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The aim of this study was to evaluate the potential usage of the eco-lining consisting of particleboards of Pinus spp. wood and sisal fibers bonded with polyurethane castor oil resin, when applied to calf-shelters covered with asbestos cement tiles. In this study, the internal temperature of the shelter, black globe temperature and relative humidity in the spring period were measured during 21 days and the ITGU, ITU and CTR comfort indexes were determined. The results indicated that the black globe temperature and the ITGU and CTR comfort indices of the eco-lining were inferior to those measured in heifers without lining. The thermographic images proved that the eco-lining decreased the transfer of heat and radiation to the interior of the installation.